Phytochemical screening of seeds of Solanum xanthocarpum - Thayalini, T.; Tharshika, B.; Tharshika, S.; Nirosh, R.; Sivatharshini, R. (Unit of Siddha Medicine, University of Jaffna, 2017)
Solanum xanthoocarpum known as Kandangattari in Tamil and Katuwelbatu in Sinhala is a perennial medicinal plant,belongs to the family of Solanaceae. In Indigenous Medicine the bark, fruit, seeds, and root of the plant are used in the treatment of various diseases. The seeds of the S.xanthocarpum are used to prepare fume in the treatment of dental caries. In the text of Sarabenthira Vaithiyamurai Siroroganithanam, fumes of the S.xanthocarpum seeds is useful in the treatment of Pat pulu (Dental caries) and Pal vali(Tooth ache). The seeds of S.xanthocarpum have Powerful sialagogue, hydragogue, expectorant, carminative and diuretic properties. Therefore, this study was aimed to screen the pytochemicals of the seeds of S.xanthocarpum, which will be used for the preparation of fume for the treatment of toothache. The fruits were collected (50 in number) from their natural habitat in Kaithady of Themaradchchy division. These were cut into two pieces and seeds were collected from the pulp. The seeds were let to dry in sun shade. The dried seeds(50g) were ground well and 5g of the seed powder was taken to prepare the extract to test the presence of secondary metabolites, such assaponin, tannins, steroids, flavonoids, glycosides and terpenoids. The Preliminary phytochemical study showed that the powder of the seed contains terpinoids, flavonoid, steroid, cardiac glycoside and tannin. In conclusion, these, secondary metabolites may possess sialogogue, hydragogue, expectorant, diuretic, carminative, anti-inflammatory, anti-spasmodic, and antimicrobial activity. Efficacy of the seed would be evaluated in clinical trial in future.
Keywords: Phytochemical screening; Solonum xanthocaroum; Seeds